Creep simulation of asymmetric effects by use of stress mode dependent weighting functions - Mahnken, Rolf (International Journal of Solids and Structures)

Theoretical and Computational Shakedown Analysis of Non-Linear Kinematic Hardening Material and Transition to Ductile Fracture - Stein, Erwin; Zhang, Genbao; Huang, Yuejun; Mahnken, Rolf; Wiechmann, Karin (Plasticity of Metals)

Parameter Identification for Inelastic Constitutive Equations Based on Uniform and Non-Uniform Stress and Strain Distributions - Mahnken, Rolf; Stein, Erwin (Plasticity of Metals)

Anisotropic creep modeling based on elastic projection operators - Mahnken, Rolf (PAMM)

Anistropic creep modeling based on elastic projection operators with applications to CMSX-4 superalloy - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)

Theoretical, numerical and identification aspects of a new model class for ductile damage - Mahnken, Rolf (International Journal of Plasticity)

Strength difference in compression and tension and pressure dependence of yielding in elasto-plasticity - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

A finite element algorithm for parameter identification of material models for fluid saturated porous media - Mahnken, Rolf; Steinmann, P. (International Journal for Numerical and Analytical Methods in Geomechanics)
Keywords: Mechanics of Materials; Geotechnical Engineering and Engineering Geology; General Materials Science; Computational Mechanics

Finite element simulation for rock salt with dilatancy boundary coupled to fluid permeation - Mahnken, Rolf; Kohlmeier, M. (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Implicit integration scheme and its consistent linearization for an elastoplastic-damage model with application to concrete - Mahnken, Rolf; Tikhomirov, D.; Stein, E. (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

Improved implementation of an algorithm for non-linear isotropic/kinematic hardening in elastoplasticity - Mahnken, Rolf (Communications in Numerical Methods in Engineering)
Keywords: Applied Mathematics; Computational Theory and Mathematics; General Engineering; Modeling and Simulation; Software

Numerical simulation of interface debonding with a combined damage/friction constitutive model - Döbert, C.; Mahnken, Rolf; Stein, E. (Computational Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

A comprehensive study of a multiplicative elastoplasticity model coupled to damage including parameter identification - Mahnken, Rolf (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

Parameter identification of gradient enhanced damage models with the finite element method - Mahnken, Rolf; Kuhl, Ellen (European Journal of Mechanics - A/Solids)
Keywords: General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; General Materials Science

Parameter estimation for a viscoplastic damage model using a gradient‐based optimization algorithm - Mahnken, Rolf; Johansson, Magnus; Runesson, Kenneth (Engineering Computations)
In this work a gradient‐based optimization method is applied in order to determine material parameters for a viscoplastic model with dynamic yield surface coupled to damage as presented in 1997. To this end a sensitivity analysis consistent with the integration scheme presented previously is performed in a systematic manner, both for strain and stress controlled experiments. The algorithm is tested in two numerical examples: first, simulated data are used, in order to re‐obtain parameters for the case of damage under monotonic loading. In the second example material parameters are obtained based on experimental data for lcf‐testing of an austenetic stainless steel, thus showing a very good agreement with respect to hardening, rate and damage effects.
Keywords: Computational Theory and Mathematics; Computer Science Applications; General Engineering; Software

A unified approach for parameter identification of inelastic material models in the frame of the finite element method - Mahnken, Rolf; Stein, Erwin (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

The identification of parameters for visco-plastic models via finite-element methods and gradient methods - Mahnken, Rolf; Stein, E (Modelling and Simulation in Materials Science and Engineering)
Keywords: Computer Science Applications; Mechanics of Materials; Condensed Matter Physics; General Materials Science; Modeling and Simulation

Efficient integration technique for generalized viscoplasticity coupled to damage - Johansson, Magnus; Mahnken, Rolf; Runesson, Kenneth (International Journal for Numerical Methods in Engineering)
Keywords: Applied Mathematics; General Engineering; Numerical Analysis

Parameter identification for viscoplastic models based on analytical derivatives of a least-squares functional and stability investigations - Mahnken, Rolf; Stein, Erwin (International Journal of Plasticity)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Parameter identification for finite deformation elasto-plasticity in principal directions - Mahnken, Rolf; Stein, Erwin (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Aspects on the finite-element implementation of the Gurson model including parameter identification - Mahnken, Rolf (International Journal of Plasticity)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Non-linear mixed isotropic-kinematic hardening coupled with damage in the framework of finite deformation elasto-plasticity - Mahnken, Rolf; Del Linz, Sandra; Stein, Erwin

Theoretische und numerische Aspekte der Berechnung thermo-mechanischer Kriechvorgänge im Steinsalz - Mahnken, Rolf; Stein, Erwin; Wetjen, Diedrich; Heemann, Ulrich (Abhandlungen der Braunschweigischen Wissenschaftlichen Gesellschaft)